Handbook of meat processing - Toldra, Fidel (Ames, Iowa : Wiley-Blackwell, 2010)
* Unparalleled international expertise of editor and contributing authors* Addresses the state of the art of manufacturing the most important meat products* Special focus on approaches to control the safety and quality of processed meats* Extensive coverage of production technologies, sanitation, packaging and sensory evaluation
1. Technologies -- 2. Products -- 3. Controls
Includes bibliographical references and index
Keywords: Meat industry and trade -- Handbooks, manuals, etc; Meat -- Handbooks, manuals, etc